Field and simulation study of the rational coal pillar width in extra‐thick coal seams. Issue 3 (6th November 2019) - He, Wenrui; He, Fulian; Zhao, Yongqiang
Abstract: The principles of mining pressure in extra‐thick coal seams are different from those of medium‐thick and thick coal seams. Field investigation, laboratory test, and simulation analysis methods were used to study the correlation between the gob‐side entry (GSE) stability and coal pillar width during longwall top coal caving mining in extra‐thick coal seams. The test site is in Datong City, Shanxi Province, China. The mining pressure in N5209 tailgate with coal pillar of 30 m is severe based on the field investigations during the N5209 panel retreat. Global constitutive double‐yield and strain‐softening models were built to study the abutment pressures and plastic failure ranges of coal seams with different thicknesses and coal pillar widths. The simulation results show that the GSE with an 8‐m coal pillar is destressed and minimal GSE deformation occurs. In addition, the abutment stress in the coal pillar decreases with increasing coal seam thickness. The field tests indicate that the GSE with an 8‐m‐wide coal pillar is stable in extra‐thick coal seams. This study provides a reference for the coal pillar design in coal mines with similar geological and mining conditions. Abstract : In this paper, the pressure environments of gob‐side entry at different coal pillar widths were explored to optimize the coal pillar width in extra‐thick coal seam through field investigation and numerical simulation. The double‐yield and strain‐softening constitutions were applied to the simulation model. Furthermore, the study results were verified by field tests.